The Violent Hero and the Heroism of Violence: Narratological Investigation of Aggressive Lyrical Content of Contemporary Punjabi Pop Songs - Kaptan Singh (Transcript: An e-Journal of Literary and Cultural Studies)
Since the last decade, the violent lyrical content of Punjabi pop songs has immensely gained the attention of the stakeholders, living in the country or abroad. Albeit the issue has been enormously discussed and debated on social platforms and the civil societies and the government bodies, time and again, have also raised their concerns against such lyrics to curb them, but there seems to be an absence of substantial academic work providing a comprehensive analysis on the issue. Moreover, the present study has conducted a lyrical content analysis of the most viewed Punjabi pop songs on YouTube between 2011 to 2020, which claims that almost 61% songs are jampacked with the lyrical content on violence and aggression. The titles, lyrics, beat, narratives, and video visuals are taken into cognizance to ascertain the elements of violence in the lyrics of contemporary Punjabi pop songs. The researcher has applied the narratological investigation method to analyse the presence, meanings, and relationships of narrative’s structure and components to understand the relation between the aggressive lyrical content and the narratives of the violent hero and the heroism of violence that is glamorizing the hero for his ideals of violence, aggression and criminal adventurism. Furthermore, the study adopts a qualitative and interpretive analysis approach to examine the aggressive lyrical content of Punjabi pop songs. The analysis focuses on the interpretation of the lyrical content of the songs in combination with narratological investigation to examine their structure and function, to identify categorization, and to quantify the content.